Green Sukuk: issues, challenges and the way forward - Syed Azman, Syed Marwan Mujahid; Shaharuddin, Siti Saffa (Routledge, 2025)
This chapter explores Green Sukuk, a Shari’ah-compliant financial instrument designed to promote investments in renewable energy and environmental assets. It addresses the key challenges and opportunities of Green Sukuk, including issues related to institutional frameworks, market dynamics, and regulatory structures. By employing a systematic literature review (SLR) following PRISMA guidelines, the study identifies significant barriers such as limited green taxonomy, high issuance costs, and greenwashing risks. It categorises challenges across three phases: issuance, allocation, and reporting, providing detailed insights into sub-issues like governance quality, political instability, and regulatory harmonisation. The findings underscore the potential of Green Sukuk to bridge gaps between Islamic finance and global sustainability goals, while calling for standardisation, enhanced awareness, and supportive policies to expand its adoption. This analysis contributes to the academic discourse on sustainable finance and informs policymakers and practitioners about the strategies needed to harness Green Sukuk’s full potential in achieving climate resilience and sustainable development.